How Catholic Parents form Religious Character in Their Children: A Qualitative Study - Anggal, Nikolaus (Educationist: Journal of Educational and Cultural Studies, 2023)
The purpose of this study is to the way they communicate with adolescents and describe the way Catholic parents set an example for adolescents to shape their religious character. Religiosity is about the depth of knowledge, sturdiness of faith, diligence in the practice of worship, depth of experience and practice as well as awareness of the religious consequences a person embraces. The method used in this research is qualitative. The results show that in parental communication to shape the religious knowledge of adolescents, parents generally do not really know the relationship with God, only a handful of parents know about it. In general, a more touching way when parents are able to practice it directly and decisively with children, especially religious practices. From the Catholic youth themselves, communication by parents has a positive impact, especially in religious practice. In the role model aspect, Catholic parents set an example directly like inviting teenagers to have first-hand experience in the real life, of the community and the church. Religious practice given by parents to adolescents is given in accordance with what parents understand which indirectly shapes the religious character of adolescents.